Role of ArgR in Activation of the ast Operon, Encoding Enzymes of the Arginine Succinyltransferase Pathway in Salmonella typhimurium - Lu, Chung-Dar (American Society for Microbiology, 1999)
The ast operon, encoding enzymes of the arginine succinyltransferase (AST) pathway, was cloned from Salmonella typhimurium, and the nucleotide sequence for the upstream flanking region was determined. The control region contains several regulatory consensus sequences, including binding sites for NtrC, cyclic AMP receptor protein (CRP), and ArgR. The results of DNase I footprintings and gel retardation experiments confirm binding of these regulatory proteins to the identified sites. Exogenous arginine induced AST under nitrogen-limiting conditions, and this induction was abolished in an argR derivative. AST was also induced under carbon starvation conditions; this induction required functional CRP as well as functional ArgR. The combined data are consistent with the hypothesis that binding of one or more ArgR molecules to a region between the upstream binding sites for NtrC and CRP and two putative promoters plays a pivotal role in modulating expression of the ast operon in response to nitrogen or carbon limitation.